2020
DOI: 10.1155/2020/9065287
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Insurance on Health Care Utilisation and Out-of-Pocket Health Expenditure in Vietnam

Abstract: Background. In recent years, health insurance (HI) has been chosen by many low- and middle-income countries to obtain an important health policy target—universal health coverage. Vietnam has recently introduced the Revised Health Insurance Law, and the effects of the voluntary health insurance (VHI) and heavily subsidised health insurance (HSHI) programmes have not yet been analysed. Therefore, this study is aimed at examining the impact of these HI programmes on the utilisation of health care services and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 37 publications
8
39
0
Order By: Relevance
“…The CBHI has decreased household per-capita health expenditure of the insured group by 17, 15, and 14 percentage points for nearest-neighbor, Kernel-based, and radius matching, respectively. This finding is similar to other studies ( 2 , 14 , 47 , 48 ).…”
Section: Resultssupporting
confidence: 93%
“…The CBHI has decreased household per-capita health expenditure of the insured group by 17, 15, and 14 percentage points for nearest-neighbor, Kernel-based, and radius matching, respectively. This finding is similar to other studies ( 2 , 14 , 47 , 48 ).…”
Section: Resultssupporting
confidence: 93%
“…particularly the out-of-pocket costs. Although, social health insurance has been shown to decrease the out-of-pocket costs of patients (21,22), they can still be notable (23,24). These out-of-pocket costs are particularly important to investigate in the context of critical care, due to its potentially high costs; which may mean they remain significant even for patients that are covered by insurance.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51] This article also found that different socioeconomic groups might have a different average level of satisfaction with health insurance. According to the finding of Thuong et al, 32 the subsidized insurance schemes (for the disadvantaged groups) did not reduce the amount of OOP payments. This limited financial effect explains why inpatients from low socioeconomic backgrounds are more likely to be dissatisfied with health insurance.…”
Section: Insurance Financial Distress and Patients' Satisfaction With...mentioning
confidence: 90%
“… 31 Meanwhile, the economic effect of health insurance was found to vary across different schemes. 32 In detail, while the voluntary scheme reduced OOP payment significantly and the health insurance programs reduced the aggregate OOP payment, the heavily subsidized health insurance schemes (for the poor and near-poor people) did not decrease the amount of OOP payment. In a study of insurance programs across the world, Lofgren et al, 33 reviewing 8755 abstracts and 118 articles about public health insurance in low- and middle-income countries, find a mixed effect of increasing insurance coverage, even though it tends to improve financial protection and health condition as well as access to health services.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation